'H, I, J, K, L, M, N, O, PEE! Get it? Pee!': Siblings' shared humour in childhood. (9th January 2019) - Paine, Amy L.; Howe, Nina; Karajian, Gassiaa; Hay, Dale F.; DeHart, Ganie
Abstract : Humour is a central feature of social interactions in childhood that has received little attention. In a sample of 86 7‐year‐old children ( M age = 7.82 years, SD  = 0.80), we investigated patterns and individual differences in spontaneous humour observed during free play with their older ( M age = 9.55 years, SD  = 0.88) or their younger sibling ( M age = 5.87 years, SD  = 0.96). We coded children's instances, categories, and responses to humour. We investigated the nature of children's humour on the dyadic and individual level. Humour was common, and siblings' production of humour was highly interdependent between play partners. Dyadic humour differed according to structural features of the sibling relationship (age, gender composition), and 7‐year‐old focal children's humour varied according to gender. This study contributes to knowledge regarding the dyadic nature of children's humour and individual patterns of humour beyond the preschool years. Statement of contribution What is already known on this subject? Humour is an integral part of children's close and intimate interactions. Children produce humour from an early age and increasingly produce more complex humour as they develop. Few studies examine children's humour with siblings and beyond the fourth year of life. What does this study add? Children's humour during free play with siblings was common and highly dyadic. Sibling dyads' humour differed according to age and gender composition. Seven‐year‐old boys produced more humour than girls.